The effectiveness of promotional strategy used to promote Newspaper in Education(NiE) of The New Straits Times Press (M) Berhad / Fara Arnizah Jamil - Jamil, Fara Arnizah (Faculty of Business and Management, 2008)
In general, promotion is the basic prominent in ensure each new firms penetrate market and keep sustaining growth for existing firms. However, after all this while, the New Straits Times (NST) had used almost all their strategies to promote Newspaper in Education (NiE) to the public especially teachers and students, but then it still does not show any positive results. Without knowing where the weakness point, the objectives of promotions cannot be achieved or targeted. Thus, the study is undertaken to examine what are the promotional strategies effectiveness level and pertinent factors that lead to the existing problem. The objective of this study is to determine the effectiveness level of the limited promotional strategies used by the New Straits Times in promoting NiE, to identify any relationship between promotional strategies that had been used in promoting NiE with level of effectiveness, to identify the most attractive promotional strategies that influence the level of effectiveness in promoting NiE, and lastly to determine which NiE activity that the respondents are interested to get involve in. The findings shows that, from all the 5 major New Straits Times (NST) promotional strategies in promoting NiE, classes have the highest effectiveness level of promotional strategy that had been used by NST in promoting NiE. The results also shows that majority of the respondents answered that classes, website (NiEXUS) and School Sponsorship Program (SSP) have the relationship with the level of effectiveness and expect the firm to use it in promoting NiE. And from the hypothesis testing, it shows that only 3 have a signifIcant relationship with the P value < 0.05.